Inovasi Pelayanan Publik OTEWE MASJO (Obat Teko Dewe Masyarakat Jogja) Dalam Peningkatan Kualitas Pelayanan Di Rumah Sakit Jogja - totok; Yuni Tursilowati, Sri (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2025)
Urgency: An effort made by the hospital to improve the quality of public services through the OTEWE MASJO Innovation to provide outpatient drug delivery services to the Yogyakarta area and its surroundings. Objective: This study aims to describe the OTEWE MASJO service innovation at Jogja Hospital and to determine the supporting and inhibiting factors of the OTEWE MASJO drug delivery service. Method: This type of descriptive qualitative research focuses on the use of public service innovation according to Bloch (2010) which includes products, processes, organizations, and communications. Data collection techniques are carried out through interviews, observations, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. Results: 1) Product, the hospital has produced products in the form of pamphlets, leaflets presented as information media for drug delivery services to homes; 2) Process, in this service, namely the procedure for obtaining patient drug delivery services from the hospital to the intended address; 3)Organization, there are special officers for OTEWE MASJO services who are given according to their duties and responsibilities; and 4) Communication, conducting socialization and coordination with related parties before this innovation is implemented to the community or patients. The average number of service user transactions is 60 transactions per day. Supporting factors are the availability of supporting facilities and infrastructure, positive community response, the existence of uncomplicated requirement procedures, good and adequate support from the Hospital Director, supported by Human Resources in implementing the OTEWE MASJO innovation and monitoring and evaluation are carried out every month through the preparation of implementation reports. The less than optimal socialization activities and dissemination of information to patients about OTEWE MASJO services is an obstacle that needs to be followed up immediately so that the target of service users increases beyond 60 transactions per day. The resulting recommendation is the need to optimize socialization activities to the community and the addition of more adequate facilities and infrastructure, for example brochures or billboards and the need for OTEWE MASJO service information through social media (Whatsapp, Facebook, Instagram, and other media).